Hybrid modulation schemes for data transmission improvement of indoor visible light communication system - Zekry, Abdelhalim; Ghandour, Christena; A. Mohammed, Nazmi; El-Rabaie, S (International Journal of Engineering and Technology, 2018)
This work enhances the bit rate characteristics, receiver sensitivity and power requirements of multicarrier modulation schemes (MCM) for visible light communication (VLC) dimming control system at bit error rate (BER) less than 10-3. This study develops the mathematical formulation for merging pulse position modulation (PPM) and overlapping pulse position modulation (OPPM) with M-ary quadrature amplitude modulation DC-Biased optical orthogonal frequency division multiplexing (M-QAM DCO OFDM), which can achieve efficient data transmission while maintaining communication quality. These schemes are then compared with the conventional merging (i.e M-QAM DCO OFDM with pulse width modulation (PWM)). Relating to the recent advances in the field, the additional comparative study is established with the latest merging platform (i.e. M-QAM DCO OFDM with multiple pulse position modulation (MPPM)).Â